2020
DOI: 10.1109/tcsii.2019.2918752
|View full text |Cite
|
Sign up to set email alerts
|

Consensus of Hybrid Multi-Agent Systems With Malicious Nodes

Abstract: This brief investigates resilient consensus problems of hybrid multi-agent systems containing both continuous-time dynamical agents and discrete-time dynamical agents. A hybrid censoring strategy is developed to reach resilient consensus for cooperative agents in the directed networks in which some Byzantine agents are present. The number, location, and dynamics of Byzantine agents are assumed to be unavailable to the cooperative agents. Sufficient conditions based on network robustness are established when th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 22 publications
0
65
0
Order By: Relevance
“…In particular, we shall consider the well-posedness and the Ulam-Hyers stability of the fixed point problem. We note that the word 'hybrid' has been used in different ways, in particular, in applicable nonlinear fields, see, e.g., [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, we shall consider the well-posedness and the Ulam-Hyers stability of the fixed point problem. We note that the word 'hybrid' has been used in different ways, in particular, in applicable nonlinear fields, see, e.g., [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…where, Equation 7shows that load a belongs to the load category B and E and thus have zero tolerance towards delay, Equation 8represents the load category C that has the minimum priority and can be scheduled anytime in the entire time horizon and Equation (9) shows that load a belongs to the semi-delay tolerant category and can only be scheduled in the pre-set allowed time slots. Where, Γ req, a denotes the required operation time of load a, and Γ EMC a provides the scheduled time interval.…”
Section: Load Delaymentioning
confidence: 99%
“…In communication and networks, the coexistence of both discrete and continuous valued agents is interpreted as hybrid system [9]. Whereas in SG, a hybrid energy system is defined as the existence of more than one energy system to accommodate the end users energy demand.…”
Section: On-site Energy Generation and Storage Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, the communication topologies were modeled. The study concluded that the voters" Additionally, [26] also investigated resilient consensus problem in hybrid multi-agent system. The hybrid multi agent system itself consists of continuous time and discrete time dynamical agents.…”
Section: B Hill Climbingmentioning
confidence: 99%